Knowledge and readiness of filipino physical educators in addressing injuries in physical education settings - Marcaida, John Louise M; Gile, Winnie Grace C; Tolentino, Julius Ceazar G; Carlos, Mary Chantelle O; Flores, Jeffrey D; Cortez, Grace Ann D (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
In school, there are a lot of lesson, skills and experiences that may took place. It is inevitable to encounter unexpected certainties during class hours, especially during Physical Education classes. There are a lot of unexpected certainties like injuries that may took place, the latter may deprove the students in attaining the knowledge and skills they may acquired during their physical education classes. Moreover, it is the teacher's primary role to keep the students safe from any harm. Thus, this study aimed to assess the knowledge and readiness of Filipino Physical Educators in addressing injuries in Physical Education settings. This mixed-method sequential explanatory research considered twenty (20) physical educators of a state-funded higher education institution were selected for the quantitative phase. Four (4) of them were selected in the qualitative phase via extreme case sampling that measured their demographic profile, knowledge, readiness, and experiences in first aid management. Using the Pearson r test manifests a negative relationship between the variables of this study and the demographic profile of the respondents/participants. As per the results of the quantitative phase and the findings of the qualitataive phase this study delineates that the Physical Educators do have a sufficient level of knowledge and readiness in terms of addressing and responding to unexpected certainties that may took place on their respective physical education classes. Furthermore, it is recommended that Physical Educators must consider a variety of strategies to improve their knowledge and readiness in dealing with injuries. With this, further knowledge and information should be obtained to strengthen and enhance the knowledge and readiness they initially have.